Regulation of replication fork progression and stability - Aragón, Luis (Henry Stewart Talks, 2009)
Replication fork anatomy, Obstacles to replication fork progression, Topological stress, Fork stabilisation, DNA repair, DNA damage bypass, Translesion synthesis, Template switching models, Fork regression mechanisms, Co-directional replication and transcription